Pengaruh Iklim Organisasi Terhadap Perilaku Produktif Karyawan Pada Bagian Sumber Daya Manusia Di Perusahaan Daerah Kebersihan Kota Bandung - Nur Azizah; Trida Gunadi (Coopetition : Jurnal Ilmiah Manajemen, 2020)
High and low of productive behavior of an employee really determines their work productivity, therefore it is necessary to foster the productive behavior. One way to foster productive behavior can be done with a conducive organizational climate. This study aims to determine how much influence the organizational climate on the productive behavior of employees in the Human Resources Section in the Regional Cleaning Company Bandung. The research method used is descriptive explanatory survey method. The data analysis technique used is a simple linear regression test and a significance test with the coefficient F. The results of the data analysis showed that the organizational climate on the Productive Behavior of employees was 32.442%. alternative hypothesis which states that there is a positive influence between organizational climate and employee productive behavior. The organizational climate and the productive behavior of employees as a whole are optimal, because the total scores obtained are both in the high category, but there are still things that must be considered, including management must be able to increase the empowerment of its employees so that the behavior and work performance of employees becomes more optimal.